Princípios para a formação corporal e cênica do cantor popular - Valéria Leite Braga (2019)
This qualitative and exploratory work aims to understand the importance of body scenic work for the pop singer, specifically in its scenic and body expression, seeking to identify principles that may guide the development of pedagogical strategies, as well as to enhance the artistic performance. For this, the following methodology was used: bibliographic review, analysis of undergraduate courses in Popular Singing at Brazilian Universities and interviews with teachers from the Music field. From the crossing and the analysis of collected data, this work defined categories on scenic and body performance of singers and presents, as a result, guiding principles intended in the research.